2017
DOI: 10.1371/journal.pone.0184854
|View full text |Cite
|
Sign up to set email alerts
|

Body composition and prediction equations using skinfold thickness for body fat percentage in Southern Brazilian adolescents

Abstract: ObjectivesThe purpose of this study was to: a) determine the nutritional status of Brazilian adolescents, and; b) present a skinfold thickness model (ST) to estimate body fat developed with Brazilian samples, using dual energy x-ray absorptiometry (DXA) as reference method.MethodsThe main study group was composed of 374 adolescents, and further 42 adolescents for the validation group. Weight, height, waist circumference measurements, and body mass index (BMI) were collected, as well as nine ST–biceps (BI), tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 23 publications
1
25
1
2
Order By: Relevance
“…In the present study, no significant association was found between the nutritional status of the survivors and the drugs used in the antineoplastic treatment. Studies have evidenced that a few medications, such as corticosteroids may increase BMI during treatment due to the increased consumption of foods, but their long term effect is still arguable [6,29,30]; nevertheless, in our study this association was not observed.…”
Section: Discussioncontrasting
confidence: 84%
“…In the present study, no significant association was found between the nutritional status of the survivors and the drugs used in the antineoplastic treatment. Studies have evidenced that a few medications, such as corticosteroids may increase BMI during treatment due to the increased consumption of foods, but their long term effect is still arguable [6,29,30]; nevertheless, in our study this association was not observed.…”
Section: Discussioncontrasting
confidence: 84%
“…There is no ideal prediction equation for body composition that is precise, accurate, affordable and practical. The predictive equation [ 25 ] used in the current study is not free from limitations. However, the strength of this equation is that the SEE values of validation remained <3%, the standard for body fat measurement as suggested by Lohman [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Then from skinfold thickness, body fat percentage was calculated using the standard formula proposed by Wagner Luis Ripka et al. (2017) [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the anthropometric indicators, waist circumference is already a consolidated index for the analysis of central fat and cardiovascular risk [37,38,39]. In addition, the circumference of the arm, hip, and calf are used to assess the nutritional status and population health [22,23,25,40,41,42,43,44,45,46]. Other factors were considered, such as low cost, reproducibility, and accessibility to the entry attributes, especially if the method is used in remote places.…”
Section: Methodsmentioning
confidence: 99%